Facile preparation, characterization and performance of noncovalently functionalized graphene/epoxy nanocomposites with poly(sodium 4-styrenesulfonate). (January 2015) - Li, Yuchao; Tang, Jianguo; Huang, Linjun; Wang, Yao; Liu, Jixian; Ge, Xiangcai; Tjong, Sie Chin; Li, Robert Kwok Yiu; Belfiore, Laurence A.
Abstract: Graphene was noncovalently functionalized with poly(sodium 4-styrenesulfonate) (PSS) and then successfully incorporated into the epoxy resin via in situ polymerization to form functional and structural nanocomposites. The morphology and structure of PSS modified graphene (PSS-g) were characterized with transmission electron microscopy, X-ray photoelectron spectroscopy and Fourier transform infrared spectroscopy. The effects of PSS-g additions on tensile, electrical and thermal properties of the epoxy/graphene nanocomposites were studied. Noncovalent functionalization improved interfacial bonding between the epoxy matrix and graphene, leading to enhanced tensile strength and modulus of resultant nanocomposites. The PSS-g additions also enhanced electrical properties of the epoxy/PSS-g nanocomposites, resulting in a lower percolation threshold of 1.2 wt%. Thermogravimetric and differential scanning calorimetric results showed the occurrence of a two-step decomposition process for the epoxy/PSS-g nanocomposites.